Prevalence Of Suboptimal Health Status Amongst General Population of Residential Area, Heavy Industries Taxila, Taxila - Mughal, Aashi; Bibi, Anwar; Riaz, Mehwish; Salman, Roma; Nisar, Nadia; Raza, Mohsin (Journal of Rawalpindi Medical College, 2024)
Objective: Determine the prevalence of suboptimal health levels and find an association between suboptimal health and lifestyle factors in a population of residential area HIT Taxila Methods: A community-based Descriptive Cross-sectional study was conducted in HIT Taxila, Jun-Nov 2023 on 400 individuals of age groups ranging from 20 to 60 years including males and females via systematic random sampling. Data was collected by Suboptimal Health Measurement (SHMS V1.0) scale including general, physical, mental and social subdomains and demographic and lifestyle factors. Chi-square was tested to determine the association between suboptimal health and demographic characteristics. Correlation was used to assess the correlation between suboptimal health and lifestyle-related factors Results: A final sample of 400 participants was included. In our sample,86(21.5%) had suboptimal health with a mean age of 29.96±9.3 years. Sub-optimal Health status was found to be significantly associated with gender(0.005), age(0.006), working status (0.015)and occupation(0.000). Health status was found to be weak and negatively correlated with social support (p-value 0.01) and a weak positive correlation was observed between nutritional habits and health status (p-value 0.05) Conclusion: SHS is significantly associated with behavior and lifestyle-related factors. To comprehensively prevent and control SHS, it is urgently needed to reduce the risk factors and enhance the protective factors among adolescents.